Jacopo Caviceo's Peregrino : Annotated English Edition and Translation - Roush, Sherry (Book collections on Project MUSE., 2023)
"Jacopo Caviceo's Peregrino (1508) was a popular Renaissance prose romance in Italy, France, and Spain. Considered the first novel written for women, Peregrino relates the courtship of two young lovers from hostile households who succeed in doing what Romeo and Juliet, among others, could not: reconcile their families and marry without resorting to suicide. Peregrino features cameos of historical celebrities who interact with fictitious characters during their many adventures, which include a Mediterranean pilgrimage, courtly celebrations, funerals, legal trials, and a journey to the Other World. The book presents female agency in psychologically developed characters and contexts and includes allusions to previous literary masterpieces, such as Homer's epics, Vergil's Aeneid, and Dante's Divine Comedy. This edition includes a detailed introduction and a biography of Jacopo Caviceo. Drawing on critical and comparative studies in a broad range of literary interests, the book sheds light on the emergence of the modern novel in the early modern period."--